Grain-oriented electrical steel sheets and intermediate steel sheets for grain-oriented electrical steel sheets
Patent Information
- Application Number
- JP2020566454
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2019-01-16
- Filing Date
- 2020-01-16
- Publication Date
- 2024-12-20
- Estimated Expiration
- 2040-01-16
AI Technical Summary
Existing grain-oriented electrical steel sheets with intermediate layers composed of silicon oxide face issues with insulating film adhesion and water resistance, leading to peeling when exposed to moisture, which affects magnetic properties and core loss.
A manufacturing process that includes controlled annealing and cooling conditions to form a film-like silicon oxide intermediate layer with specific oxide density and minimal internal oxides, enhancing adhesion and resistance to peeling.
The process results in grain-oriented electrical steel sheets with improved insulating film adhesion and water resistance, maintaining low core loss and magnetic properties even under bending and moisture exposure.
Abstract
Description
[Technology Field]
[0001] This invention relates to grain-oriented electrical steel sheets, intermediate steel sheets for grain-oriented electrical steel sheets, and methods for manufacturing the same. This application claims priority based on Japanese Patent Application No. 2019-5200, filed in Japan on January 16, 2019, and the contents of that application are incorporated herein by reference. [Background technology]
[0002] Grain-oriented electrical steel sheets are used as core materials for transformers and other electrical equipment. These sheets require specific magnetic properties, such as low iron loss.
[0003] Typically, a coating is formed on the surface of grain-oriented electrical steel sheets to reduce iron loss. This coating reduces iron loss in a single sheet by applying tension to the grain-oriented electrical steel sheet. Furthermore, when grain-oriented electrical steel sheets are laminated and used as a core, this coating ensures electrical insulation between the sheets, thereby reducing iron loss in the core.
[0004] In the case of grain-oriented electrical steel sheets with a coating, a finish annealed coating mainly composed of forsterite (Mg2SiO4) is formed on the surface of the base steel sheet, and an insulating coating is further formed on the surface of the finish annealed coating. In other words, in this case, the coating on the base steel sheet includes a finish annealed coating and an insulating coating. The finish annealed coating and the insulating coating each perform both insulating and tension-applying functions to the base steel sheet.
[0005] The finish annealed film, mainly composed of forsterite (Mg2SiO4), is formed during a finish annealing process that induces secondary recrystallization of the steel sheet. This process involves a reaction between the annealing separator, primarily composed of magnesia (MgO), and the base steel sheet during a heat treatment held at 600-1200°C for 30 hours or more.
[0006] The insulating film is formed by applying a coating solution containing, for example, phosphoric acid or phosphate, colloidal silica, and chromic anhydride or chromate to a steel sheet after finish annealing, and then baking and drying it at 300 to 950°C for 10 seconds or more.
[0007] For insulating coatings to exhibit their insulating and tension-imparting functions to the base steel plate, high adhesion between these coatings (finish annealing coating and insulating coating) and the base steel plate is required.
[0008] Conventionally, the above-mentioned adhesion has been ensured primarily by the anchoring effect caused by the irregularities at the interface between the base steel sheet and the finish-burned pure coating. However, these irregularities at the interface also hinder the movement of magnetic domain walls when the grain-oriented electrical steel sheet is magnetized. Therefore, these irregularities at the interface also hinder the reduction of iron loss in grain-oriented electrical steel sheets.
[0009] When a finish annealing coating such as a forsterite coating is formed, irregularities occur at the interface between the base steel sheet and the finish annealing coating. Therefore, in order to reduce iron loss, it is effective to suppress the formation of the finish annealing coating and smooth the surface of the base steel sheet.
[0010] For example, Patent Documents 1 and 2 propose a technique for smoothing the surface of a base steel sheet without the presence of a finish coating mainly composed of forsterite, in order to promote low iron loss.
[0011] Specifically, Patent Document 1 discloses a method for manufacturing grain-oriented electrical steel sheets, in which the finish annealing film is removed by pickling or the like, and the surface of the base steel sheet is smoothed by chemical polishing or electrolytic polishing. Furthermore, Patent Document 2 discloses a method for manufacturing grain-oriented electrical steel sheets, in which an annealing separating agent containing alumina (Al2O3) is used during finish annealing to suppress the formation of the finish annealing film itself and to smooth the surface of the base steel sheet.
[0012] However, when forming an insulating film by contacting (directly onto) a smooth base steel plate surface that does not have a finish annealing film, as obtained by the techniques described in Patent Documents 1 and 2, there was a problem in that the insulating film did not adhere well to the base steel plate surface (sufficient adhesion could not be obtained).
[0013] In response to such problems, for example, in Patent Documents 3, 4, 5, and 6, in order to enhance the adhesion of the insulating film to the surface of the smoothed mother steel plate, a technique of forming an intermediate layer (undercoat film) between the mother steel plate and the insulating film has been proposed.
[0014] Patent Document 3 discloses a method of applying an aqueous solution of phosphate or alkali metal silicate to the surface of the mother steel plate to form an intermediate layer on the surface of the mother steel plate. Further, Patent Documents 4 to 6 disclose a method of forming an external oxidation type silicon oxide film as an intermediate layer by subjecting the mother steel plate to a heat treatment of several tens of seconds to several minutes with appropriately controlled temperature and atmosphere.
[0015] According to the intermediate layers proposed in Patent Documents 3 to 6, to some extent, an effect can be obtained in improving the adhesion of the insulating film to the mother steel plate and suppressing the decrease in iron loss due to smoothing of the unevenness at the interface between the mother steel plate and the film. However, in recent years, further improvement in film adhesion has been demanded. In response to such requirements, new technologies shown in Patent Documents 7, 8, 9, 10, 11, and 12 have been proposed.
[0016] Patent Document 7 discloses a technique of forming granular external oxides in addition to an external oxidation film mainly composed of silicon oxide on the surface of the mother steel plate. Further, Patent Document 8 discloses a technique of controlling the cavities of an external oxidation type silicon oxide film mainly composed of silicon oxide.
[0017] Patent Documents 9 to 11 disclose a technique of modifying an external oxidation film mainly composed of silicon oxide by incorporating metallic iron or metal-based oxides (for example, Si-Mn-Cr oxide, Si-Mn-Ca-Ti oxide, Fe oxide, etc.).
[0018] Patent Document 12 discloses a grain-oriented electrical steel sheet having a multi-layer intermediate layer including an oxide film mainly composed of silicon oxide generated by an oxidation reaction and a coating layer mainly composed of silicon oxide formed by coating and baking.
[0019] As described above, by using an external oxide film mainly composed of silicon oxide as an intermediate layer, a grain-oriented electrical steel sheet has been proposed that ensures adhesion of the insulating film to the base steel sheet even if the surface of the base steel sheet is smoothed, and that also exhibits excellent magnetic properties.
[0020] Incidentally, when grain-oriented electrical steel sheets are used as the core of a transformer, such as in wound cores or EI cores, the sheets are processed by bending or other methods to achieve the desired shape. Furthermore, when grain-oriented electrical steel sheets with an intermediate layer processed to the desired shape are used in a transformer, the insulating coating may peel off due to a reaction with moisture in the air or moisture in the oil in which the core is immersed. Therefore, grain-oriented electrical steel sheets used as the core of a transformer, such as in wound cores or EI cores, are required to have not only good adhesion of the insulating coating to the base steel sheet, but also water resistance. However, in the patent documents describing the techniques for grain-oriented electrical steel sheets having an intermediate layer mainly composed of silicon oxide, no literature mentions the peeling of the insulating film by water. [Prior art documents] [Patent Documents]
[0021] [Patent Document 1] Japanese Patent Publication No. 49-096920 [Patent Document 2] International Publication No. 2002 / 088403 [Patent Document 3] Japanese Patent Publication No. 05-279747 [Patent Document 4] Japanese Patent Publication No. 06-184762 [Patent Document 5] Japanese Patent Publication No. 09-078252 [Patent Document 6] Japanese Patent Publication No. 07-278833 [Patent Document 7] Japanese Patent Application Publication No. 2002-322566 [Patent Document 8] Japanese Patent Application Publication No. 2002-363763 [Patent Document 9] Japanese Patent Application Publication No. 2003-313644 [Patent Document 10] Japanese Patent Publication No. 2003-171773 [Patent Document 11] Japanese Patent Publication No. 2002-348643 [Patent Document 12] Japanese Patent Publication No. 2004-342679 [Overview of the project] [Problems that the invention aims to solve]
[0022] The present invention has been made in view of the above problems. The object of the present invention is to provide a grain-oriented electrical steel sheet having an intermediate layer mainly composed of silicon oxide, which achieves improved adhesion of the insulating film and improved water resistance, which had not been recognized as a problem in the past, as well as an intermediate steel sheet for the grain-oriented electrical steel sheet, and a method for manufacturing the same. Furthermore, excellent water resistance means that the peeling and progression of the insulating film due to corrosion when water adheres to the surface of the grain-oriented electrical steel sheet can be suppressed. [Means for solving the problem]
[0023] The gist of this invention is as follows: (1) A base steel plate, an intermediate layer formed on the surface of the base steel plate and mainly composed of silicon oxide, and an insulating film formed on the surface of the intermediate layer, wherein the number density of oxides in a region with a depth of 10 μm from the surface of the base steel plate toward the interior of the base steel plate is 0.020 particles / μm 2 The grain-oriented electrical steel sheet is as follows: In the region where the insulating coating has peeled off after a bending test using a mandrel in accordance with JIS K 5600-5-1 (1999), the area ratio of the intermediate layer remaining without peeling off is 20% or more.
[0024] (2) A hot rolling step to produce a hot-rolled steel sheet by heating the slab to 1280°C or below and then hot rolling it; a hot-rolled sheet annealing step to produce an annealed steel sheet by performing hot-rolled sheet annealing on the hot-rolled steel sheet; a cold rolling step to produce a cold-rolled steel sheet by performing cold rolling on the annealed steel sheet; a decarburization annealing step to produce a base steel sheet by performing decarburization annealing on the cold-rolled steel sheet; an annealing separation agent application step to apply an annealing separation agent having a composition containing alumina (Al2O3): 50% by mass or more and the remainder being magnesia (MgO): 0 to 50% by mass to the base steel sheet; a finish annealing step to perform finish annealing on the base steel sheet after the annealing separation agent application step; and the degree of oxidation P of the base steel sheet after the finish annealing step, which is expressed as the ratio of the partial pressure of water vapor to the partial pressure of hydrogen in the temperature range of 1100 to 500°C. H2O / P H2 A method for manufacturing grain-oriented electrical steel sheets, comprising: a cooling step of cooling in an atmosphere with a temperature of 0.30 to 100,000; an intermediate layer formation step of heat-treating the base steel sheet after the cooling step to form an intermediate layer mainly composed of silicon oxide on the surface of the base steel sheet; and an insulating film formation step of forming an insulating film on the surface of the intermediate layer after the intermediate layer formation step.
[0025] (3) A base steel plate and a film-like oxide formed on the surface of the base steel plate, wherein the film-like oxide exists to cover the surface of the base steel plate in a film-like manner, and the number density of the oxide in a region with a depth of 10 μm from the outermost surface of the base steel plate toward the interior of the base steel plate is 0.020 particles / μm 2 The following are intermediate steel sheets for grain-oriented electrical steel sheets.
[0026] (4) A hot rolling step to produce a hot-rolled steel sheet by heating the slab to 1280°C or below and then hot rolling it; a hot-rolled sheet annealing step to produce an annealed steel sheet by performing hot-rolled sheet annealing on the hot-rolled steel sheet; a cold rolling step to produce a cold-rolled steel sheet by performing cold rolling on the annealed steel sheet; a decarburization annealing step to produce a base steel sheet by performing decarburization annealing on the cold-rolled steel sheet; an annealing separation agent application step to apply an annealing separation agent having a composition containing alumina (Al2O3): 50% by mass or more and the remainder being magnesia (MgO): 0 to 50% by mass to the base steel sheet; a finish annealing step to perform finish annealing on the base steel sheet after the annealing separation agent application step; and the degree of oxidation P of the base steel sheet after the finish annealing step, which is expressed as the ratio of the partial pressure of water vapor to the partial pressure of hydrogen in the temperature range of 1100 to 500°C. H2O / P H2 A method for manufacturing an intermediate steel sheet for grain-oriented electrical steel sheets, comprising a cooling step of cooling in an atmosphere with a temperature of 0.30 to 100,000. [Effects of the Invention]
[0027] According to the present invention, it is possible to provide a grain-oriented electrical steel sheet having an intermediate layer mainly composed of silicon oxide, which exhibits high adhesion of the insulating film and high water resistance. Furthermore, the present invention provides an intermediate steel sheet for this grain-oriented electrical steel sheet and a method for manufacturing them. [Modes for carrying out the invention]
[0028] The inventors of this invention investigated methods to solve the above-mentioned problems.
[0029] The inventors first observed areas where the insulating film had peeled off due to moisture in the air or moisture in the oil in which the iron core was immersed (hereinafter referred to as the "insulating film peeling area"). As a result, the inventors noticed that the structure of the areas where the insulating film had peeled off due to water was correlated with the structure of the areas where the insulating film had peeled off due to bending deformation.
[0030] Specifically, it is as follows: The inventors first performed a bending test on a grain-oriented electrical steel sheet having an intermediate layer and an insulating film, as specified in JIS K 5600-5-1 (1999). After the bending test, the areas where the insulating film had peeled off on the surface of the test specimen (the inner surface of the bend) were observed using a scanning electron microscope (SEM). The observation revealed that in the areas where the insulating film had peeled off (insulating film peeled-off areas), there were areas where the insulating film had peeled off but the intermediate layer remained (intermediate layer remaining areas), and areas where both the insulating film and the intermediate layer had peeled off, exposing the surface of the base steel sheet (base steel sheet exposed areas).
[0031] Both the region where the intermediate layer remains and the region where the base steel sheet is exposed appeared in grain-oriented electrical steel sheets when the insulating coating was peeled off by water. Furthermore, when the insulating coating was peeled off by water, the total area of the base steel sheet exposed region was larger than the total area of the region where the intermediate layer remains.
[0032] Based on the above findings, the inventors considered the following regarding the peelability of the insulating film by water in grain-oriented electrical steel sheets having an intermediate layer mainly composed of silicon oxide. When a portion of the insulating film peels off due to bending or the like, the larger the proportion of the total area of the base steel sheet exposed within the peeled insulating film region, the greater the rate of peeling progression of the insulating film by water. In other words, the peeling of the insulating film by water is further accelerated. The reason for this is not clear, but it is thought that corrosion occurs in the exposed area of the base steel sheet due to contact with water, and this corrosion accelerates the peeling of the insulating film. On the other hand, the larger the proportion of the total area of the intermediate layer remaining within the peeled insulating film region, the smaller the rate of peeling progression of the insulating film by water. Furthermore, the degree of peeling of the insulating film by water correlates with the proportion of the intermediate layer remaining area in the peeled insulating film region when a bending test specified in JIS K 5600-5-1 (1999) is performed.
[0033] Furthermore, the inventors investigated a method to increase the area ratio of the remaining intermediate layer in the insulating film peeling region after the bending test described above. In this investigation, they focused on the change in adhesion between the base steel sheet and the intermediate layer by controlling the surface condition of the base steel sheet before the formation of the intermediate layer.
[0034] As a result, the inventors found that by selecting an appropriate annealing separating agent and further controlling the atmosphere during the cooling process of the finish annealing, and by appropriately controlling the oxidation state of the base steel sheet surface at the end of the finish annealing, the adhesion of the intermediate layer formed thereafter is improved.
[0035] Specifically, the magnesia (MgO) content of the annealing separating agent is set to 50% by mass or less, so that the surface layer of the base steel sheet is free of internally oxidized oxides at least when secondary recrystallization is complete. The point at which secondary recrystallization is complete means the point at which cooling of the finish annealing begins.
[0036] Here, "internal oxidation" refers to a state in which, when observed in the cross-section of a steel sheet, the oxide does not penetrate to the surface of the base steel sheet but exists surrounded by the base steel sheet. Examples of internal oxidation oxides (hereinafter also called internal oxides) include forsterite (Mg2SiO4), silica (Si-O), and mullite (Al-Si-O). When internal oxidation oxides are formed on the base steel sheet, the iron loss of grain-oriented electrical steel sheets deteriorates.
[0037] Furthermore, regarding the atmosphere in the temperature range of 1100-500°C during the cooling process of finish annealing, the degree of oxidation (P) is expressed as the ratio of the partial pressure of water vapor to the partial pressure of hydrogen. H2O / P H2 The coefficient of oxidation () is set to a range of 0.30 to 100000, and an external oxidation type oxide is formed on the surface of the base steel sheet.
[0038] Here, "external oxidation type" refers to a state in which the oxide almost uniformly covers the surface of the base steel sheet, rather than the oxide form that penetrates into the interior of the base steel sheet as in the internal oxidation type, that is, a state in which the surface of the base steel sheet is covered in a film-like manner. Therefore, external oxidation type oxides may also be referred to as film-like oxides below. External oxidation type oxides are compounds of elements of the base steel sheet and oxygen. In this embodiment, for example, there are oxides in which iron oxide (FeO, Fe2O3) and feallite (Fe-Si-O) take on a layered structure.
[0039] Technically, "internal oxidation" and "external oxidation" are not classified by the forms described above, but rather by their oxidation mechanisms. However, such a classification in the invention would be complex, and it would be difficult to confirm the mechanism after oxidation. Therefore, in this embodiment, we will use the classification based on the form of the oxide resulting from the oxidation described above.
[0040] The reason why controlling the oxide on the surface of the base steel sheet after finish annealing increases the area ratio of the remaining intermediate layer in the insulation film delamination region after bending tests is not entirely clear, but the following factors may be considered. The intermediate layer formed during the intermediate layer formation process is generally thought to be formed during the oxidation of the Si-containing base steel sheet. However, if oxides already exist on the surface of the base steel sheet after finish annealing, it is necessary to consider the effect of their reduction on the intermediate layer. In the wide temperature range of 1100 to 500°C after finish annealing, externally oxidized oxides that form relatively slowly as the temperature decreases are thought to be film-like and have high continuity with the base steel sheet, such as changes in elemental concentration and structure in the thickness direction. It is thought that as such oxides are reduced and the intermediate layer is formed, the atomic bonding structure between the base steel sheet surface and the intermediate layer becomes stronger, improving adhesion.
[0041] When oxides penetrate the base steel sheet, they are not reduced during the formation of the intermediate layer, leaving an uneven surface at the interface between the base steel sheet and the intermediate layer. This hinders the movement of magnetic domain walls when the electrical steel sheet is magnetized. Therefore, it is considered necessary to avoid the formation of internally oxidized oxides as much as possible.
[0042] Based on the above findings, a grain-oriented electrical steel sheet (grain-oriented electrical steel sheet according to this embodiment), an intermediate steel sheet for the grain-oriented electrical steel sheet according to this embodiment, and a method for manufacturing them will be described. The grain-oriented electrical steel sheet according to this embodiment includes a base steel sheet, an intermediate layer formed on the surface of the base steel sheet and mainly composed of silicon oxide, and an insulating film formed on the surface of the intermediate layer. The number density of oxides in a region with a depth of 10 μm from the surface of the base steel sheet toward the inside of the base steel sheet (a region starting from the surface of the base steel sheet and ending at a depth position of 10 μm in the depth direction (thickness direction) from the surface to the inside) is 0.020 pieces / μm 2 is as follows. Further, after a bending test performed using a mandrel in accordance with JIS K 5600-5-1 (1999), the area ratio of the intermediate layer remaining region where the intermediate layer remains without peeling in the region where the insulating film has peeled is 20% or more.
[0043] [Grain-oriented electrical steel sheet] The grain-oriented electrical steel sheet according to this embodiment is obtained by forming an intermediate layer and an insulating film on an intermediate steel sheet for grain-oriented electrical steel sheets. In other words, the grain-oriented electrical steel sheet according to this embodiment includes a base steel sheet and a film formed in contact with the surface of the base steel sheet. This film includes an intermediate layer formed in contact with the surface of the base steel sheet and an insulating film formed in contact with the surface of the intermediate layer.
[0044] [Base steel sheet] The grain-oriented electrical steel sheet according to this embodiment is characterized by the number density of oxides in the surface layer portion of the base steel sheet and the structure of the film (intermediate layer and insulating film) formed on the surface of the base steel sheet. Specifically, the number density of oxides in a region with a depth of 10 μm from the surface of the base steel sheet toward the inside of the base steel sheet is 0.020 pieces / μm 2 or less. In this embodiment, a state where the number density of oxides is 0.020 pieces / μm 2 or less is expressed as "substantially no internal oxides exist". That is, in the surface layer portion of the base steel sheet included in the grain-oriented electrical steel sheet according to this embodiment (a region with a depth of 10 μm from the surface of the base steel sheet toward the inside of the base steel sheet), there are substantially no internal oxides in a state where oxides have penetrated into the inside of the base steel sheet. The number density of oxides in a region with a depth of 10 μm from the surface of the base steel sheet toward the inside of the base steel sheet is 0.020 pieces / μm 2If the iron content is excessive, the iron loss of grain-oriented electrical steel sheets deteriorates.
[0045] The number density of oxides (internal oxides) in the above region can be determined by the following method. Specifically, the cross-section of the steel sheet perpendicular to the rolling direction is observed with a scanning electron microscope (SEM) at a magnification of 5000x or more, and the number density of oxides with an equivalent circular diameter of 0.1 μm or more is measured in a region extending 100 μm in the direction parallel to the surface of the steel sheet and 10 μm in depth from the surface (outermost surface) of the base steel sheet towards the interior of the base steel sheet.
[0046] Furthermore, in the grain-oriented electrical steel sheet according to this embodiment, after a bending test using a mandrel in accordance with JIS K 5600-5-1 (1999), the area ratio of the intermediate layer remaining without peeling in the region where the insulating film has peeled off is 20% or more. The diameter of the mandrel is, for example, 10 to 16 mm.
[0047] If the base steel sheet is exposed, contact with water will cause corrosion of the base steel sheet, which is thought to further accelerate the peeling of the insulating film. On the other hand, if the adhesion between the base steel sheet and the intermediate layer is high, the intermediate layer will remain even in areas where the insulating film has peeled off. In other words, even if the insulating film peels off, if the intermediate layer remains, corrosion of the base steel sheet can be suppressed, and further peeling of the insulating film can be suppressed. For this reason, in the grain-oriented electrical steel sheet according to this embodiment, the adhesion between the base steel sheet and the intermediate layer is enhanced.
[0048] The base steel sheet of the grain-oriented electrical steel sheet according to this embodiment is controlled such that, after a bending test, the area ratio of the intermediate layer remaining without peeling in the region where the insulating film has peeled off (hereinafter sometimes referred to as the intermediate layer retention rate) is 20% or more, thus providing excellent water resistance. If the area ratio of the intermediate layer remaining is less than 20%, the water resistance will decrease. The intermediate layer retention rate may be 100%.
[0049] The base sheet of the grain-oriented electrical steel sheet according to this embodiment is not particularly limited in terms of chemical composition and microstructure, as long as it satisfies the number density of internal oxides and the area ratio of the remaining intermediate layer region. For example, the base sheet of this embodiment may be any base sheet used in a general grain-oriented electrical steel sheet. An example of the base sheet of the grain-oriented electrical steel sheet according to this embodiment will be described below.
[0050] [Chemical composition of the base steel sheet] The chemical composition of the base sheet of the grain-oriented electrical steel sheet according to this embodiment can be the same as that of a base sheet in a general grain-oriented electrical steel sheet. The chemical composition of the base sheet may include, for example, the following elements. Unless otherwise specified, the "%" used for the content of each element in the chemical composition of the base sheet means mass percent. Numerical limits indicated by "~" include both a lower limit and an upper limit within that range.
[0051] The base sheet of the grain-oriented electrical steel sheet according to this embodiment contains, for example, Si: 0.50 to 7.00%, C: 0.005% or less, and N: 0.0050% or less, with the remainder being Fe and impurities. The reasons for limiting the typical example of the chemical composition of the base sheet of the grain-oriented electrical steel sheet according to this embodiment will be explained below.
[0052] Si: 0.50–7.00% Silicon (Si) increases the electrical resistance of grain-oriented electrical steel sheets, thereby reducing iron loss. If the Si content is less than 0.50%, this effect cannot be fully obtained. Therefore, it is preferable that the Si content be 0.50% or more. More preferably, the Si content is 1.50% or more, and even more preferably 2.50% or more. On the other hand, if the Si content exceeds 7.00%, the saturation magnetic flux density of the base steel sheet decreases, and the iron loss of the grain-oriented electrical steel sheet deteriorates. Therefore, it is preferable that the Si content be 7.00% or less. More preferably, the Si content is 5.50% or less, and even more preferably 4.50% or less.
[0053] C: 0.005% or less Carbon (C) forms compounds in the base steel sheet, degrading the iron loss of the grain-oriented electrical steel sheet. Therefore, the C content is preferably 0.005% or less. More preferably, the C content is 0.004% or less, and even more preferably 0.003% or less. On the other hand, it is preferable to have as low a carbon content as possible, so 0% is acceptable, but carbon may be present as an impurity in the steel. Therefore, the carbon content may be greater than 0%.
[0054] N: 0.0050% or less Nitrogen (N) forms compounds in the base steel sheet, degrading the iron loss of the grain-oriented electrical steel sheet. Therefore, the N content is preferably 0.0050% or less. More preferably, the N content is 0.0040% or less, and even more preferably 0.0030% or less. On the other hand, it is preferable to have as low an N content as possible, so 0% is acceptable, but N may be present as an impurity in the steel. Therefore, the N content may be greater than 0%.
[0055] The remainder of the chemical composition of the base steel sheet consists of Fe and impurities. Here, "impurities" refers to elements that are introduced during the industrial manufacturing of the base steel sheet from components contained in the raw materials or components mixed in during the manufacturing process, and which do not substantially affect the effects obtained by the grain-oriented electrical steel sheet according to this embodiment.
[0056] [Optional element] The chemical composition of the base steel sheet is basically to contain the elements listed above, with the remainder being Fe and impurities. However, to improve magnetic properties or solve manufacturing problems, one or more arbitrary elements may be included in place of some of the Fe. Examples of arbitrary elements that may be included in place of some of the Fe include the following elements. These elements do not need to be included, so the lower limit is 0%. On the other hand, if the content of these elements is too high, precipitates will form, degrading the iron loss of the grain-oriented electrical steel sheet, or ferrite transformation will be suppressed, resulting in insufficient GOSS orientation or a decrease in saturation magnetic flux density, thus degrading the iron loss of the grain-oriented electrical steel sheet. Therefore, even when they are included, it is preferable to keep them within the following ranges. Acid-soluble Al: 0.0065% or less, Mn: 1.00% or less, S and Se: Total of 0.001% or less. Bi: 0.010% or less, B: 0.0080% or less, Ti: 0.015% or less, Nb: 0.020% or less, V: 0.015% or less, Sn: 0.50% or less, Sb: 0.50% or less, Cr: 0.30% or less, Cu: 0.40% or less, P: 0.50% or less, Ni: 1.00% or less, Mo: 0.10% or less. Furthermore, "S and Se: 0.001% or less in total" means that the base steel sheet may contain only either S or Se, and the content of either S or Se may be 0.001% or less, or the base steel sheet may contain both S and Se, and the total content of S and Se may be 0.001% or less.
[0057] The chemical composition of the base steel sheet of the grain-oriented electrical steel sheet according to the above embodiment is obtained by employing the manufacturing method of the grain-oriented electrical steel sheet according to the present embodiment using a slab having the chemical composition described later.
[0058] The chemical composition of the base steel sheet of the grain-oriented electrical steel sheet according to this embodiment can be measured using spark optical emission spectrometry (Spark-OES). If the content is trace, it can be measured using inductively coupled plasma-mass spectrometry (ICP-MS) as needed. Acid-soluble aluminum can be measured by ICP-MS using the filtrate obtained after heating and decomposing the sample with acid. Carbon and sulfur (C) can be measured using combustion-infrared absorption spectroscopy, and nitrogen (N) can be measured using inert gas fusion-thermal conductivity spectroscopy.
[0059] [Surface roughness of the base steel plate] The surface roughness of the base steel sheet is not particularly limited. However, if irregularities are formed on the surface of the base steel sheet, the iron loss reduction effect may be hindered. To avoid such interference with the iron loss reduction effect, for example, the surface roughness of the base steel sheet is preferably 1.0 μm or less in terms of Ra (arithmetic mean roughness). A more preferable upper limit for the arithmetic mean roughness Ra of the base steel sheet surface is 0.8 μm, and an even more preferable upper limit is 0.6 μm. The lower limit for the arithmetic mean roughness Ra of the base steel sheet surface may be 0.001 μm.
[0060] The arithmetic mean roughness Ra of the surface of the above base steel plate is measured by the following method. A sample is taken from the cross-section of the grain-oriented electrical steel sheet, with the observation surface perpendicular to the rolling direction. The surface roughness of the base steel sheet on the obtained observation surface is measured. Specifically, if a coating such as a finish hardened film or an intermediate layer is formed on the surface of the base steel sheet, the interface between the base steel sheet and the intermediate layer on the observation surface (cross-section) is measured. If no coating is formed and the surface of the base steel sheet is exposed, the position coordinates of the base steel sheet surface in the thickness direction on the observation surface (cross-section) are measured with an accuracy of 0.01 μm or more, and the arithmetic mean roughness Ra is calculated in accordance with JIS B 0601 (2001). The measurement is performed over a continuous 2 mm range (total of 20,000 points) at 0.1 μm intervals in a direction parallel to the surface of the base steel sheet, and the arithmetic mean roughness Ra is determined using a reference length of 2 mm. The arithmetic mean roughness Ra is determined at at least 5 arbitrary locations on the surface of the base steel sheet using the above method, and the average value of the Ra values obtained at each location is defined as the arithmetic mean roughness Ra of the base steel sheet surface. This observation can be performed using a scanning electron microscope (SEM), and image processing is practical for measuring positional coordinates.
[0061] [Middle class] The intermediate layer is formed in contact with the surface of the base steel sheet, which is substantially free of internal oxides. The intermediate layer is an external oxide film mainly composed of silicon oxide. Here, "mainly composed of silicon oxide" means that the composition of the intermediate layer satisfies the following conditions: Fe content of less than 30 atomic%, P content of less than 5 atomic%, Si content of less than 50 atomic%, 20 atomic%, O content of less than 80 atomic%, 50 atomic%, and Mg content of 10 atomic% or less.
[0062] The intermediate layer is a layer placed between the base steel sheet and the insulating film, and is effective in ensuring close contact between the base steel sheet and the insulating film. The intermediate layer is formed, for example, by reducing a film-like oxide formed by performing a specific cooling process in the finish annealing process, as will be explained in the manufacturing process described later.
[0063] The silicon oxide that forms the main component of the intermediate layer is preferably SiOx (x=1.0 to 2.0), and more preferably SiOx (x=1.5 to 2.0), because silicon oxide is more stable in this form. If sufficient heat treatment is applied to the surface of the base steel sheet to form silicon oxide, silica (SiO2) can be formed.
[0064] In an intermediate layer formed by heat treatment of a base steel plate under conditions of holding the plate at a temperature range of 600 to 1150°C for 10 to 600 seconds in an atmosphere consisting of 20 to 50% hydrogen by volume, the remainder being nitrogen and impurities, with a dew point of -20 to 2°C, silicon oxide exists in an amorphous state. An intermediate layer mainly composed of amorphous silicon oxide formed under these heat treatment conditions is preferable because it has high strength to withstand thermal stress, and is a dense material with a relatively low modulus of elasticity that can easily relieve thermal stress.
[0065] The base sheet of grain-oriented electrical steel contains a high concentration of Si (for example, Si: 0.50 to 7.00 mass%). As a result, a strong chemical affinity is developed between the silicon oxide-based intermediate layer and the base sheet, causing the intermediate layer and the base sheet to adhere firmly.
[0066] The thickness of the intermediate layer is not particularly limited. If it is 2 nm or more, the adhesion of the insulating film to the base steel plate is more effectively improved, so the preferred thickness of the intermediate layer is 2 nm or more, and more preferably 5 nm or more. If the thickness of the intermediate layer is 400 nm or less, defects such as voids and cracks within the intermediate layer are effectively suppressed. Therefore, the preferred thickness of the intermediate layer is 400 nm or less, and more preferably 300 nm or less. Making the intermediate layer as thin as possible while ensuring film adhesion shortens the formation time and contributes to high productivity, as well as suppressing a decrease in the packing ratio when used as an iron core. Therefore, the thickness of the intermediate layer is more preferably 100 nm or less, and even more preferably 50 nm or less.
[0067] The method for measuring the thickness of the intermediate layer is as follows: The cross-section of the intermediate layer is observed and measured using a TEM (transmission electron microscope) with an electron beam diameter of 10 nm. Specifically, for example, for TEM observation, a sample is cut out so that it has an observation cross-section parallel to the thickness direction of the plate. In the observation cross-section of the sample, five or more measurement positions are selected from a measurement area that includes the intermediate layer, the aforementioned base steel plate, and the insulating film described later, and that are separated from each other by 2 μm or more in the width direction, with a width of 10 μm or more in the direction parallel to the surface of the base steel plate. The thickness of the intermediate layer is then measured using TEM. The average of the measured values is taken as the thickness of the intermediate layer. When measuring the thickness of the intermediate layer at each measurement position within the measurement area using TEM, the layer existing between the aforementioned base steel plate and insulating film is measured as the intermediate layer.
[0068] [Insulating coating] The insulating film is formed on the surface of the intermediate layer. Known insulating films can be used. For example, the insulating film mainly consists of a compound containing P, O, and Si, and may also contain Cr. The insulating film imparts tension to the base steel sheet, reducing iron loss as a single sheet of steel. Furthermore, the insulating film ensures electrical insulation between grain-oriented electrical steel sheets when they are laminated together.
[0069] As the insulating film becomes thinner, the tension applied to the base steel plate decreases and the insulating properties also decline. Therefore, the thickness of the insulating film is preferably 0.1 μm or more, and more preferably 0.5 μm or more. On the other hand, if the thickness of the insulating film exceeds 10 μm, there is a risk of cracks occurring in the insulating film during the formation stage. Therefore, the thickness of the insulating film is preferably 10 μm or less, and more preferably 5 μm or less. The thickness of the insulating film can be measured by observing the cross-section of the insulating film (or grain-oriented electrical steel sheet) with a TEM (transmission electron microscope). The specific measurement method is the same as that used to measure the thickness of the intermediate layer.
[0070] The insulating film may be subjected to magnetic domain refinement treatment, if necessary, by laser, plasma, mechanical methods, etching, or other techniques, to form localized micro-strain regions or grooves.
[0071] [Characteristics of the coating structure of grain-oriented electrical steel sheets] In the grain-oriented electrical steel sheet according to this embodiment, after a bending test performed using a mandrel in accordance with JIS K 5600-5-1 (1999), the area ratio of the intermediate layer remaining without peeling in the region where the insulating film has peeled off is controlled to be 20% or more. Therefore, when a bending test is performed in accordance with JIS K 5600-5-1 (1999), the area ratio of the intermediate layer remaining without peeling in the region where the insulating film has peeled off will be 20% or more. The area ratio of the intermediate layer remaining is preferably 30% or more, and more preferably 40% or more. The intermediate layer remaining rate may be 100%.
[0072] The area ratio of the remaining intermediate layer is determined by the following method. A rectangular sample is taken from the grain-oriented electrical steel sheet, measuring 10 mm perpendicular to the rolling direction and 150 mm parallel to the rolling direction. Of the test specimen, the observation surface of the 10 mm × 150 mm sample is the surface including the coating. A bending test is performed on the collected sample in accordance with JIS K 5600-5-1 (1999). Specifically, the collected sample is wrapped around a round bar (mandrel) with a diameter of 10 to 16 mm and bent 180°. The test specimen is then bent back.
[0073] The observation surface (the inner surface of the bend) after the bending test is observed using a COMPO image obtained from a scanning electron microscope (SEM), and the areas on the observation surface where the insulating film has peeled off (insulating film peeling areas) are identified. Specifically, the COMPO image of the observation surface is converted into a 256-level monochrome image, and the area with less than 50% of the grayscale from the white side is determined to be the area where the insulating film has peeled off. The total area of the identified insulating film peeling areas is then calculated.
[0074] The evaluation area for insulation film delamination in the bending test is defined by the following formula. If the insulation film delamination area is less than 5% of the evaluation area, the bending diameter is reduced (a smaller diameter mandrel is used) and the evaluation is re-evaluated. If the re-evaluation shows that the insulation film delamination area is 5% or more of the evaluation area, the area ratio of the remaining intermediate layer is calculated. (Evaluation area for insulation film removal) = (Diameter of mandrel) × (Pi) ÷ 2
[0075] Furthermore, the region where the insulating film has been peeled off on the observation surface is mapped using an energy-dispersive X-ray spectrometer (SEM-EDS) to obtain the Si concentration distribution in atomic percent. The maximum and minimum Si concentrations are identified from the obtained Si concentration distribution. The region satisfying the following equation is defined as the intermediate layer remaining region. (Si concentration in the region) > {(maximum Si concentration) + (minimum Si concentration)} / 2 However, if the maximum and minimum Si concentrations satisfy the following equation, the area ratio of the remaining intermediate layer region shall be considered 0%. (Maximum Si concentration) - (Minimum Si concentration) < 5 atoms %
[0076] The area ratio of the remaining intermediate layer (%) is defined as the ratio of the total area of the remaining intermediate layer region on the observation surface to the total area of the delaminated insulating film region (delaminated film portion) in the EDS mapping. In other words, the area ratio of the remaining intermediate layer region is defined by the following formula. Area ratio of the remaining intermediate layer = (Total area of the remaining intermediate layer) / (Total EDS mapping area) × 100 Here, the total EDS mapping area is 15 mm². 2 This concludes the explanation. If the area ratio of the remaining intermediate layer is insufficient in a single test specimen, it may be calculated as the average value using multiple test specimens.
[0077] If, after a bending test conducted using a mandrel in accordance with JIS K 5600-5-1 (1999), the area ratio of the remaining intermediate layer in the region where the insulating film has peeled off is 20% or more, then the adhesion of the intermediate layer to the base steel sheet is sufficiently high. Therefore, in this case, even if a part of the insulating film has peeled off, the base steel sheet is covered by the intermediate layer, which can suppress the progression of peeling of the insulating film due to corrosion when water adheres to it. In other words, the water resistance of the grain-oriented electrical steel sheet can be improved.
[0078] [Regarding intermediate steel sheets for grain-oriented electrical steel sheets] The intermediate steel sheet for grain-oriented electrical steel according to this embodiment comprises a base steel sheet and a film-like oxide formed on the surface of the base steel sheet. The film-like oxide exists so as to cover the surface of the base steel sheet in a film-like manner. Furthermore, the number density of oxides (internal oxides) present in the base steel sheet in a region with a depth of 10 μm from the surface toward the interior of the base steel sheet is 0.020 particles / μm 2 The following applies: This intermediate steel sheet is a steel sheet used in the manufacture of the grain-oriented electrical steel sheet according to this embodiment, and is a steel sheet after finish annealing (more specifically, after the cooling process described later and before the intermediate layer formation process). By forming an intermediate layer mainly composed of silicon oxide on the surface of the base steel sheet and further forming an insulating film on the surface of the intermediate layer, the grain-oriented electrical steel sheet according to this embodiment is obtained.
[0079] In the intermediate steel sheet for grain-oriented electrical steel sheets according to this embodiment, the surface of the base steel sheet is substantially free of internal oxides, which are oxides that have penetrated into the interior of the base steel sheet. If internal oxides are present after finish annealing, these internal oxides are not reduced during intermediate layer formation, and the internal oxides remain on the surface of the base steel sheet. These internal oxides hinder the movement of magnetic domain walls when the grain-oriented electrical steel sheet is magnetized, and the iron loss of the grain-oriented electrical steel sheet deteriorates. On the other hand, the surface of the base steel plate has a film-like oxide layer that covers the surface of the base steel plate, formed by external oxidation.
[0080] The term "substantially absent internal oxides" specifically means that the number density of oxides in a region extending 10 μm in the thickness direction from the surface (outermost surface) of the base steel plate towards the interior of the plate is 0.020 particles / μm (a region starting from the surface of the base steel plate and ending at a depth of 10 μm in the thickness direction). 2 The following can be shown: The number density of oxides in this region can be determined by observing the cross-section of the steel plate with a scanning electron microscope (SEM) at a magnification of 5000x or higher, and measuring the number density of oxides with an equivalent circle diameter of 0.1 μm or larger in a region extending 100 μm in a direction parallel to the surface of the steel plate and 10 μm inward from the surface of the base steel plate into the base steel plate. The number density of these internal oxides does not change even when an intermediate layer or an insulating film is formed.
[0081] The oxide forms a film-like structure covering the entire surface of the base steel sheet by adjusting the conditions of the cooling process after finish annealing. Specifically, in the cooling process after finish annealing, the base steel sheet is cooled, and the degree of oxidation (P), which is expressed as the ratio of the partial pressure of water vapor to the partial pressure of hydrogen, is measured in the temperature range where the base steel sheet is 1100 to 500°C. H2O / P H2 This is obtained by cooling in an atmosphere with an oxidation degree of 0.30 to 100,000. When the oxidation degree is between 0.30 and 100,000, the film-like oxide takes on a layered structure and uniformly covers the surface of the base steel sheet. As a result, it is thought that a strong intermediate layer is formed with the base steel sheet in the next process, improving the adhesion of the insulating film.
[0082] The film-like oxides after finish annealing are mainly iron oxide (FeO, Fe2O3) and fierite (Fe-Si-O). Therefore, it is thought that in the atmosphere that mainly forms the intermediate layer in the next process, the Fe in the iron oxide is reduced and replaced by an intermediate layer mainly composed of externally oxidized silicon oxide.
[0083] Next, a method for manufacturing grain-oriented electrical steel sheets according to this embodiment, and a method for manufacturing intermediate steel sheets for grain-oriented electrical steel sheets according to this embodiment will be described. A coating (intermediate layer and insulating coating) having the above-described characteristics can be manufactured, for example, by the manufacturing method described later.
[0084] The intermediate steel sheet for grain-oriented electrical steel sheet according to this embodiment is obtained by a manufacturing method comprising the following steps (S0) to (S62). (S0) Preparation process (S1) Hot rolling process (S2) Hot rolled plate annealing process (S3) Cold rolling process (S4) Decarburization annealing process (S5) Annealing Separating Agent Coating Process (S61) Finish annealing process (S62) Cooling process
[0085] The grain-oriented electrical steel sheet according to this embodiment is obtained by a manufacturing method that further comprises steps (S7) and (S8) in addition to the above steps (S0) to (S62). (S7) Intermediate layer formation process (S8) Insulating film formation process
[0086] The following describes each step.
[0087] [S0: Preparation process] In the preparation process, the slab is prepared. The method of manufacturing the slab is not limited, but the following methods are examples. Molten steel is produced (melted). Slabs are manufactured using the molten steel. Slabs may be manufactured by continuous casting. Ingots may be manufactured using the molten steel, and slabs may be manufactured by bloc rolling of the ingots. Slabs may be manufactured by other methods. The thickness of the slab is not particularly limited. The thickness of the slab is, for example, 150 to 350 mm. Preferably, the thickness of the slab is 220 to 280 mm. As the slab, so-called thin slabs with a thickness of 10 to 70 mm may be used. When thin slabs are used, rough rolling before finish rolling can be omitted in the hot rolling process.
[0088] [Chemical composition of the slab] The chemical composition of the slab can be set to, for example, the following range, taking into account the changes in content during the manufacturing process from slab to grain-oriented electrical steel sheet, in order to obtain the chemical composition of the base steel sheet in a typical grain-oriented electrical steel sheet. Unless otherwise specified, the "%" used for the content of each element in the chemical composition of the slab refers to mass percent. Numerical limits indicated by "~" include both a lower and upper limit. Si: 0.80–7.00%, C: 0.085% or less, Acid-soluble Al: 0.010-0.065%, N: 0.0040–0.0120%, Mn: 0.05–1.00%, S and Se: 0.003–0.015% in total, Remainder: Fe and impurities. The following describes each element.
[0089] Si: 0.80–7.00% Silicon (Si) increases the electrical resistance of grain-oriented electrical steel sheets, thereby reducing iron loss. If the Si content is less than 0.80%, γ transformation occurs during finish annealing, which impairs the crystal orientation of the grain-oriented electrical steel sheet. On the other hand, if the Si content exceeds 7.00%, the cold workability decreases, and cracks are more likely to occur during cold rolling. Therefore, the preferred Si content is 0.80 to 7.00%. The Si content is more preferably 2.00% or more, and even more preferably 2.50% or more. Furthermore, the Si content is more preferably 4.50% or less, and even more preferably 4.00% or less.
[0090] C: 0.085% or less Carbon (C) is inevitably present. Although C is an effective element for controlling the primary recrystallization structure, it adversely affects the magnetic properties. Therefore, it is preferable that the C content be 0.085% or less. The lower the C content, the better. However, when considering productivity in industrial production, a carbon content of 0.020% or more is preferable, and 0.040% or more is more preferable. C is purified in the decarburization annealing and finish annealing processes described later, and the C content becomes 0.005% or less after the finish annealing process.
[0091] Acid soluble Al: 0.010-0.065% Acid-soluble aluminum (Al) combines with nitrogen to precipitate as (Al,Si)N and functions as an inhibitor. Secondary recrystallization is stable when the acid-soluble Al content is 0.010 to 0.065%. Therefore, the acid-soluble Al content is preferably 0.010 to 0.065%. The acid-soluble Al content is more preferably 0.015% or more, and even more preferably 0.020% or more. From the viewpoint of the stability of secondary recrystallization, the acid-soluble Al content is more preferably 0.045% or less, and even more preferably 0.035% or less. Acid-soluble aluminum, if it remains after finish annealing, forms compounds that degrade the iron loss of grain-oriented electrical steel sheets. Therefore, it is preferable to minimize the amount of acid-soluble aluminum contained in the steel sheet after finish annealing by purification during the finish annealing process. Depending on the conditions of the finish annealing, the steel sheet after finish annealing may not contain any acid-soluble aluminum.
[0092] N: 0.0040–0.0120% Nitrogen (N) combines with Al to function as an inhibitor. If the N content is less than 0.0040%, a sufficient amount of inhibitor will not be produced. The N content is more preferably 0.0050% or more, and even more preferably 0.0060% or more. On the other hand, if the N content exceeds 0.0120%, blistering, a type of defect, is more likely to occur in the steel sheet. Therefore, the preferred N content is 0.0040 to 0.0120%. The N content is more preferably 0.0110% or less, and even more preferably 0.0100% or less. N is purified during the finish annealing process, and after the finish annealing process, the N content is 0.0050% or less.
[0093] Mn: 0.05–1.00% Manganese (Mn) combines with S or Se to form MnS or MnSe, which functions as an inhibitor. Secondary recrystallization is stable when the Mn content is in the range of 0.05 to 1.00%. Therefore, the preferred Mn content is 0.05 to 1.00%. The Mn content is preferably 0.06% or more, and more preferably 0.07% or more. Furthermore, the Mn content is more preferably 0.50% or less, and even more preferably 0.20% or less. Depending on the finish annealing conditions, the steel sheet may not contain Mn after finish annealing.
[0094] S and Se: Total 0.003–0.015% Sulfur (S) and selenium (Se) combine with manganese (Mn) to form MnS or MnSe, which function as inhibitors. Secondary recrystallization is stable when the total content of S and Se is 0.003 to 0.015%. Therefore, the preferred total content of S and Se is 0.003 to 0.015%. If sulfur (S) and sediment (Se) remain after finish annealing, they form compounds that degrade the iron loss of grain-oriented electrical steel sheets. Therefore, it is preferable to minimize the amount of S and Se contained in the steel sheet after finish annealing by purifying it during the finish annealing process. Depending on the conditions of the finish annealing, the steel sheet after finish annealing may not contain S or Se.
[0095] Here, "the total content of S and Se is 0.003 to 0.015%" means that the slab may contain only S or Se, with the content of either S or Se being 0.003 to 0.015%, or the slab may contain both S and Se, with the total content of S and Se being 0.003 to 0.015%.
[0096] The remainder of the chemical composition of the slab used in the manufacture of the grain-oriented electrical steel sheet according to this embodiment consists of Fe and impurities. Here, "impurities" refers to elements that are introduced from components contained in the raw materials or components mixed in during the manufacturing process when industrially manufacturing the base steel sheet of the grain-oriented electrical steel sheet according to this embodiment, and that do not substantially adversely affect the effects obtained by the grain-oriented electrical steel sheet according to this embodiment.
[0097] [Optional element] The chemical composition of the slab may include one or more arbitrary elements in place of some of the Fe, taking into consideration the enhancement of inhibitory function through compound formation and the influence on magnetic properties. Examples of arbitrary elements that may be included in place of some of the Fe include the following elements. These elements are optional and do not need to be included, so the lower limit is 0%. Bi: 0.010% or less, B: 0.080% or less, Ti: 0.015% or less, Nb: 0.20% or less, V: 0.15% or less, Sn: 0.50% or less, Sb: 0.50% or less, Cr: 0.30% or less, Cu: 0.40% or less, P: 0.50% or less, Ni: 1.00% or less, and Mo: 0.10% or less.
[0098] [S1: Hot rolling process] In the hot rolling process, a prepared slab is subjected to hot rolling using a hot rolling mill to produce a steel sheet (hot-rolled steel sheet). Specifically, first, the slab is heated. For heating, for example, the slab is placed in a well-known heating furnace or a well-known soaking furnace and heated. The preferred heating temperature for the slab is 1280°C or lower. By keeping the heating temperature of the slab below 1280°C, various problems that occur when heating at temperatures higher than 1280°C (such as the need for a dedicated heating furnace and the large amount of molten scale) can be avoided. The preferred upper limit for the heating temperature of the slab is 1250°C. The heating time for the slab should be 40 to 120 minutes.
[0099] There is no particular lower limit to the heating temperature of the slab. However, if the heating temperature is too low, hot rolling may become difficult, and productivity may decrease. Therefore, the heating temperature should be set within a range of 1280°C or lower, taking productivity into consideration. A preferred lower limit for the heating temperature of the slab is 1100°C.
[0100] It is also possible to omit the slab heating process altogether and begin hot rolling after casting, before the slab temperature drops.
[0101] Hot-rolled steel sheets are manufactured by hot-rolling a heated slab using a hot-rolling mill. The hot-rolling mill, for example, comprises a roughing mill and a finishing mill located downstream of the roughing mill. The roughing mill comprises a row of roughing stands. Each roughing stand includes multiple rolls arranged vertically. Similarly, the finishing mill comprises a row of finishing stands. Each finishing stand includes multiple rolls arranged vertically. After the heated steel material is rolled in the roughing mill, it is further rolled in the finishing mill to produce hot-rolled steel sheets.
[0102] The thickness of hot-rolled steel sheets produced by hot rolling is not particularly limited. For example, the thickness of a hot-rolled steel sheet may be 3.5 mm or less. The finishing temperature in the hot rolling process (the temperature of the steel sheet at the exit of the finishing rolling stand where the steel sheet is finally rolled down in the finishing rolling mill) is, for example, 900 to 1000°C. Hot-rolled steel sheets are manufactured through the hot rolling process described above.
[0103] [S2: Hot rolled plate annealing process] In the hot-rolled sheet annealing process, the hot-rolled steel sheet obtained in the hot-rolling process is subjected to hot-rolled sheet annealing to obtain an annealed steel sheet.
[0104] The conditions for hot-rolled sheet annealing can be those that are well known. For example, the annealing temperature (furnace temperature in the hot-rolled sheet annealing furnace) is 750 to 1200°C. The holding time at the annealing temperature is, for example, 30 to 600 seconds.
[0105] [S3: Cold Rolling Process] In the cold rolling process, cold rolling is performed on annealed steel sheets that have been annealed after being hot-rolled.
[0106] In the cold rolling process, cold rolling may be performed only once or multiple times. If cold rolling is performed multiple times, intermediate annealing for softening purposes may be performed after cold rolling, and then cold rolling may be performed again. Known methods can be used for intermediate annealing conditions. Before cold rolling the annealed steel sheet, it may be pickled.
[0107] When multiple cold rolling processes are carried out without an intermediate annealing process, it may be difficult to obtain uniform properties in the manufactured grain-oriented electrical steel sheet. On the other hand, when multiple cold rolling processes are carried out, and an intermediate annealing process is performed between each cold rolling process, the magnetic flux density of the manufactured grain-oriented electrical steel sheet may be low. Therefore, the number of cold rolling processes and the presence or absence of an intermediate annealing process are determined according to the properties required for the final manufactured grain-oriented electrical steel sheet and the manufacturing cost.
[0108] In one or more cold rolling processes, the preferred cumulative cold rolling percentage (cumulative reduction) is 80% or more, and more preferably 90% or more. The preferred upper limit for the cumulative cold rolling percentage is 95%. Here, the cumulative cold rolling percentage (%) is defined as follows: Cumulative cold rolling rate (%) = (1 - thickness of cold-rolled steel sheet after the last cold rolling / thickness of annealed steel sheet before the start of the first cold rolling) × 100
[0109] The cold-rolled steel sheet obtained by the cold-rolling process is wound into a coil. The thickness of the cold-rolled steel sheet is not particularly limited, but in order to further reduce iron loss, it is preferable to have a thickness of 0.35 mm or less, and more preferably 0.30 mm or less.
[0110] [S4: Decarburization annealing process] In the decarburization annealing process, decarburization annealing is performed on the cold-rolled steel sheet obtained in the cold-rolling process. Decarburization annealing is carried out, for example, by the following method: A cold-rolled steel sheet is placed in a heat treatment furnace. The temperature of the heat treatment furnace (decarburization annealing temperature) is set to, for example, 800 to 950°C and held for 30 to 180 seconds, and the atmosphere of the heat treatment furnace is a humid atmosphere containing hydrogen and nitrogen. By performing decarburization annealing under the above conditions, primary recrystallization occurs, and carbon is removed from the steel sheet.
[0111] [S5: Annealing Separating Agent Application Process] In the annealing separation agent application step, the annealing separation agent is applied to the surface of the base steel sheet after decarburization annealing. In general methods for manufacturing grain-oriented electrical steel sheets, an annealing separation agent containing 90% by mass or more of MgO is used. However, in this case, a glass film with an uneven shape is formed on the surface of the steel sheet. When a glass film with an uneven shape is formed, the iron loss deteriorates. Therefore, in the method for manufacturing grain-oriented electrical steel sheets according to this embodiment, an annealing separation agent having a composition containing 50% by mass or more of alumina (Al2O3) and the remainder being magnesia (MgO): 0 to 50% by mass is used. If the MgO content is 50% by mass or less, it is possible to suppress the formation of internal oxides that cause uneven shapes at the interface with the steel sheet while forming a film-like oxide. The preferred upper limit for MgO in the annealing separation agent is 45% by mass, and the more preferred upper limit is 40% by mass.
[0112] The preferred lower limit for MgO is 10% by mass, and the more preferred lower limit is 15% by mass. If the MgO content is 10% by mass or more, the formation of mullite (Al-Si-O), a type of internal oxide, can be suppressed. This suppresses the deterioration of iron loss due to internal oxides. Al2O3 may be present in a 100% by mass ratio. Alternatively, Al2O3 may be present in a 90% or less by mass ratio, or a 85% or less by mass ratio. Furthermore, Al2O3 may be present in a 55% or more by mass ratio, or a 60% or more by mass ratio.
[0113] [S61: Finishing annealing process] In the finish annealing process, the base steel sheet (coil) is subjected to finish annealing after the annealing release agent application process. This process allows the annealing release agent to be baked on and also induces secondary recrystallization in the base steel sheet.
[0114] When finish annealing is performed, the surface of the base steel sheet is oxidized, and a film-like oxide is formed on the surface of the base steel sheet. For example, when an annealing separating agent mainly composed of Al2O3 is applied, a film-like oxide is formed, mainly composed of oxides of Fe and Si, which are the main components of the steel sheet.
[0115] The finish annealing conditions are as follows, for example. The furnace atmosphere during finish annealing is not particularly limited and any well-known atmosphere is acceptable.
[0116] Finish annealing temperature: 1100-1300℃ Holding time at finish annealing temperature: 20-24 hours If the finish annealing temperature is 1100 to 1300°C, sufficient secondary recrystallization occurs, improving the magnetic properties of the grain-oriented electrical steel sheet. Furthermore, the aforementioned film-like oxide is formed on the surface of the base steel sheet. If the finish annealing temperature is below 1100°C, sufficient secondary recrystallization may not occur. If it exceeds 1300°C, the coil strength may decrease at high temperatures, causing the coil to deform. Furthermore, if the holding time is less than 20 hours, purification failure may occur. On the other hand, holding times exceeding 24 hours are undesirable because they reduce productivity.
[0117] [S62: Cooling process] After the finish annealing process, a cooling process is carried out to cool the base steel sheet. At this time, in the temperature range where the base steel sheet is 1100 to 500°C, the degree of oxidation (P H2O / P H2 Cooling is performed in a gas atmosphere with a pressure of 0.30 to 100,000. The temperature range of 1100 to 500°C is the temperature range in which oxidation of the base steel sheet can occur. Therefore, by controlling oxidation across this wide temperature range, a desirable film-like oxide can be formed.
[0118] If the degree of oxidation in the temperature range of 1100 to 500°C is less than 0.30, the oxide itself will not form. In this case, the adhesion of the intermediate layer to the base steel sheet in the subsequent intermediate layer formation process will decrease. As a result, in the manufactured grain-oriented electrical steel sheet, after a bending test using a mandrel in accordance with JIS K 5600-5-1 (1999), the area ratio of the intermediate layer remaining without peeling in the area where the insulating film has peeled off will be less than 20%. Consequently, the peel resistance (water resistance) of the insulating film to water will decrease. On the other hand, if the degree of oxidation in the above temperature range exceeds 100,000, internal oxides will form. In this case, the internal oxides will remain without being reduced even after the intermediate layer is formed, so the iron loss of the grain-oriented electrical steel sheet will deteriorate. Therefore, the degree of oxidation of the atmosphere in the temperature range where the base steel plate is 1100 to 500°C is 0.30 to 100000.
[0119] The cooling method for the base steel plate in the temperature range of 1100 to 500°C is not particularly limited. One example of a cooling method is to turn off the heater during batch annealing and allow it to cool.
[0120] Through the above process, a base steel sheet with substantially no internal oxides and a film-like oxide formed on it, i.e., an intermediate steel sheet for grain-oriented electrical steel according to this embodiment, is manufactured. The intermediate steel sheet for grain-oriented electrical steel according to this embodiment is substantially free of internal oxides. Therefore, the surface of the base steel sheet after the finish annealing process is smooth and unevenness is suppressed. For example, the arithmetic mean roughness Ra of the base steel sheet surface is 1.0 μm or less. Therefore, grain-oriented electrical steel obtained using this intermediate steel sheet can achieve low iron loss.
[0121] The above finish annealing process also serves as purification annealing. Purification annealing removes inhibitor components such as Al, N, Mn, S, and Se from the steel.
[0122] [S7: Intermediate layer formation process] In the intermediate layer formation process, the intermediate steel sheet for the grain-oriented electrical steel sheet according to this embodiment is subjected to heat treatment. This forms an intermediate layer that is in contact with the surface of the base steel sheet and is mainly composed of silicon oxide.
[0123] The heat treatment conditions for intermediate layer formation are not particularly limited. When forming an intermediate layer to a thickness of 2 to 400 nm, it is preferable to hold the film at a temperature range of 300 to 1150°C for 5 to 120 seconds, and more preferably at a temperature range of 600 to 1150°C for 10 to 60 seconds. Furthermore, from the viewpoint of preventing oxidation of the inside of the base steel sheet, it is preferable to use a reducing atmosphere during heating up to the temperature range where the temperature will be maintained and during temperature maintenance, and more preferably a nitrogen atmosphere mixed with hydrogen. Examples of a nitrogen atmosphere mixed with hydrogen include an atmosphere consisting of 5 to 50 volume% hydrogen and the remainder being nitrogen and impurities, with a dew point of -20 to 2°C. In particular, an atmosphere consisting of 10 to 35 volume% hydrogen and the remainder being nitrogen and impurities, with a dew point of -10 to 0°C is preferred.
[0124] In the intermediate layer formation process, the aforementioned film-like oxide is reduced to form an intermediate layer mainly composed of silicon oxide. As a result, the adhesion of the intermediate layer to the base steel sheet is improved. Consequently, in the manufactured grain-oriented electrical steel sheet, the area ratio of the intermediate layer remaining without peeling in the region where the insulating film has peeled off after a bending test using a mandrel in accordance with JIS K 5600-5-1 (1999) is 20% or more.
[0125] The heat treatment in the intermediate layer formation process may be a separate heat treatment performed solely for the purpose of forming the intermediate layer. The heat treatment may also be performed simultaneously with or consecutively with the heat treatment performed for the purpose of forming the insulating film. If a separate heat treatment is performed solely for the purpose of forming the intermediate layer, a separate heat treatment for the purpose of forming the insulating film is performed afterward.
[0126] [S8: Insulating film formation process] In the insulating film formation process, an insulating film consisting of a compound containing P, O, and Si is formed on the surface of the intermediate layer. The insulating film may further contain Cr.
[0127] In the insulating film formation process, a coating solution containing phosphoric acid or phosphate, colloidal silica, and optionally chromic anhydride or chromate is applied to the surface of the intermediate layer. After applying the coating solution, baking is performed to form an insulating film that contacts the surface of the intermediate layer.
[0128] Examples of phosphates include those of Ca, Al, Mg, and Sr. The colloidal silica is not particularly limited, and its particle size can be used as appropriate. Furthermore, various elements and compounds may be added to the coating solution to improve various properties.
[0129] The baking conditions are not particularly limited. For example, the baking conditions consist of hydrogen, water vapor, and nitrogen, and the degree of oxidation of the atmosphere (P H2O / P H2 This condition involves holding the sample at a temperature range of 300 to 1150°C for 5 to 300 seconds in an atmosphere of 0.0001 to 1.0.
[0130] In the insulating film formation process, the above coating solution is applied to the surface of the intermediate layer, and the degree of oxidation of the atmosphere (P H2O / P H2 It is preferable to bake the coating in an atmosphere with an oxidation degree of 0.001 to 0.1, holding it at a temperature of 300°C to 900°C for 10 seconds or more. If the oxidation degree of the atmosphere is 0.001 or higher, the phosphate, which is the main constituent phase of the insulating film, is less likely to decompose, and the water resistance is further enhanced. If the oxidation degree of the atmosphere is 0.1 or lower, iron loss can be further reduced.
[0131] In the insulating film formation process, it is preferable to cool the steel sheet in an atmosphere in which the oxidation degree of the above gas is kept low so that the insulating film and intermediate layer do not change after baking. The cooling conditions can be general conditions, but for example, an atmosphere consisting of hydrogen, nitrogen, water vapor and impurities, with a low oxidation degree (P H2O / PH2 The atmosphere should be less than 0.01.
[0132] The manufacturing method for grain-oriented electrical steel sheets according to this embodiment may further include steps that are generally performed in the manufacturing method of grain-oriented electrical steel sheets. For example, the manufacturing method for grain-oriented electrical steel sheets according to this embodiment may further include a nitriding treatment step, which is performed after the decarburization annealing step and before the application of the annealing separation agent, to increase the N content in the base steel sheet. This is because the magnetic flux density can be stably improved even if the temperature gradient applied to the steel sheet at the boundary between the primary recrystallization region and the secondary recrystallization region is low. Any general treatment can be used as the nitriding treatment. For example, this could include annealing in an atmosphere containing a gas with nitriding ability such as ammonia, or finishing annealing of a decarburized annealed steel sheet to which an annealing separation agent containing a powder with nitriding ability such as MnN has been applied.
[0133] The present invention is not limited to the embodiments described above. The embodiments described above are illustrative, and any configuration that is substantially identical to the technical idea described in the claims of the present invention and achieves similar effects is included within the technical scope of the present invention. [Examples]
[0134] The present invention will be specifically described below with reference to examples. In the following examples, the conditions are merely one example of conditions adopted to confirm the feasibility and effectiveness of the present invention. The present invention is not limited to this one example of conditions. The present invention can adopt various conditions as long as they do not depart from the spirit of the invention and achieve the objectives of the present invention.
[0135] A slab was prepared with a chemical composition containing Si:3.30%, C:0.050%, acid-soluble Al:0.030%, N:0.0080%, Mn:0.10%, S and Se:0.005% in total, with the remainder being Fe and impurities. The above slab was heated to 1150°C for 60 minutes to produce a hot-rolled steel sheet with a thickness of 2.6 mm. The hot-rolled steel sheet was then annealed to produce an annealed steel sheet. The annealing conditions were annealing at a temperature of 900°C for 120 seconds. The resulting annealed steel sheet was then cold-rolled to produce a cold-rolled steel sheet with a final thickness of 0.23 mm.
[0136] The obtained cold-rolled steel sheets were subjected to decarburization annealing. The decarburization annealing conditions were 850°C for 90 seconds in a humid atmosphere consisting of 75% hydrogen by volume and the remainder being nitrogen and impurities.
[0137] An annealing separation agent containing MgO in the proportions shown in Table 1 was applied to the surface of the obtained steel plate. In the annealing separation agent, the remainder other than MgO was Al2O3.
[0138] A base steel sheet was obtained by applying an annealing release agent to a steel sheet, drying it, performing finish annealing, and then cooling it. The conditions for finish annealing were to heat the base steel sheet to 1200°C in a hydrogen-nitrogen mixed atmosphere at a heating rate of 15°C / hour, and then hold it at 1200°C in a hydrogen atmosphere for 20 hours. After finish annealing, the base steel sheet was cooled by turning off the heater during batch annealing. The degree of oxidation (P), expressed as the ratio of the partial pressure of water vapor to the partial pressure of hydrogen, was measured in the temperature range where the base steel sheet was 1100-500°C. H2O / P H2 The results were as shown in Table 1. Furthermore, the chemical composition of the base steel sheet after finish annealing contained Si: 3.30%, C: 0.002% or less, acid-soluble Al: 0.0030% or less, N: 0.0020% or less, Mn: 0.10%, S and Se: 0.0005% or less in total, with the remainder consisting of Fe and impurities.
[0139] [Table 1]
[0140] For test numbers 1 to 12, a heat treatment was performed on the base steel sheet after finish annealing to simultaneously form an intermediate layer and an insulating film. The conditions for the intermediate layer and insulating film formation process were as follows: A coating solution was applied to the surface of the steel plate. The composition of the coating solution for test numbers 1 to 10 was phosphate: 50%, colloidal silica: 45%, and chromic anhydride: 5% by mass. The composition of the coating solution for test numbers 11 to 12 was phosphate: 55% and colloidal silica: 45% by mass. The steel plate to which the coating solution was applied was subjected to a reaction involving hydrogen, nitrogen, water vapor, and impurities, with a degree of oxidation (P). H2O / P H2 In an atmosphere of 0.1, the temperature was heated to 850°C and held for 30 seconds.
[0141] For test numbers 13 to 17, the intermediate layer formation process and the insulating film formation process were carried out separately. After finish annealing, the base steel sheet was heat-treated to form the intermediate layer. The conditions for the intermediate layer formation process were as follows: Degree of oxidation (P H2O / P H2 In an atmosphere of 0.01, the temperature was heated to 850°C and held for 30 seconds. Furthermore, an insulating film was formed on the base steel sheet with the intermediate layer. In the insulating film formation process, a coating solution was applied to the surface of the intermediate layer. The composition of the coating solution was 60% phosphate and 40% colloidal silica. The steel sheet coated with the coating solution was heated to 850°C in an atmosphere consisting of 75% hydrogen by volume and the remainder being nitrogen and impurities, held for 30 seconds to form an insulating film, and then cooled to room temperature.
[0142] [Cross-sectional observation] For each test number, specimens with a cross-section perpendicular to the rolling direction were taken from the grain-oriented electrical steel sheet, and the cross-section was observed using a scanning electron microscope (SEM). The magnification was 10,000x, and the region from the steel sheet surface to a depth of 10 μm was observed over a 100 μm range in a direction parallel to the steel sheet surface. In test numbers 1 to 8, 11 to 15, and 17, almost no internal oxides were formed. In other words, the number density of oxides with an equivalent circle diameter of 0.1 μm or more in the region from the surface of the base steel sheet to a depth of 10 μm into the base steel sheet was 0.020 particles / μm 2The results were as follows: On the other hand, in test numbers 9 and 16, a large amount of internal oxides, mainly silicon oxide, were formed on the surface of the base steel plate, creating irregularities. In other words, the number density of oxides with an equivalent circular diameter of 0.1 μm or more in a region 10 μm deep from the surface of the base steel plate towards the interior of the base steel plate was 0.020 particles / μm 2 The results were exceptional. In test number 10, a large amount of internal oxides, mainly forsterite with an equivalent circular diameter of 0.1 μm or more, were formed on the surface of the base steel plate, creating irregularities.
[0143] For each test number of the grain-oriented electrical steel sheet, cross-sectional observation using TEM (transmission electron microscope) confirmed the composition of the intermediate layer, as determined by electron diffraction patterns and EDX (energy-dispersive X-ray analysis), that the Fe content was less than 30 atomic%, the P content was less than 5 atomic%, the Si content was less than 50 atomic%, and 20 atomic% or more, the O content was less than 80 atomic%, and 50 atomic% or more, and the Mg content was 10 atomic% or less.
[0144] [Adhesion Test] The adhesion test was conducted in accordance with the bending resistance test of JIS K 5600-5-1 (1999). Test specimens measuring 80 mm in the rolling direction and 40 mm in the direction perpendicular to rolling were taken from grain-oriented electrical steel sheets numbered 1 to 17. The taken test specimens were wrapped around mandrels with a diameter of 10 mm or 16 mm. For the adhesion test, a 180° bend was performed using the Type 1 test apparatus described in the bending resistance test of JIS K 5600-5-1 (1999). The total area of the portion where the insulating film had peeled off (insulating film peeling area) was measured on the inner surface of the bent test specimen after bending. Subsequently, the area ratio of the remaining intermediate layer was determined using the method described above. The results are shown in Table 1. Note that the bending diameter in Table 1 refers to the diameter of the mandrel. If the diameter of the wrapped mandrel is 10 mm, the area of insulation film stripping is 7.5 mm². 2 The following conditions were deemed to provide excellent adhesion. Furthermore, when the diameter of the wrapped mandrel was 16 mm, the insulation film peeling area was 5.0 mm². 2 The following criteria were deemed to provide excellent adhesion.
[0145] The evaluation area for insulation film delamination in the bending test was defined by the following formula. If the insulation film delamination area was less than 5% of the evaluation area, the bending diameter (mandrel diameter) was reduced and the evaluation was re-evaluated. If the re-evaluation showed that the insulation film delamination area was 5% or more of the evaluation area, the area ratio of the remaining intermediate layer was calculated. (Evaluation area) = (Bending diameter) × (Pi) ÷ 2
[0146] The area ratio of the remaining intermediate layer was determined by mapping the identified insulating film delamination region using an energy-dispersive X-ray spectrometer (SEM-EDS) to obtain the Si concentration distribution. From the obtained Si concentration distribution, the maximum and minimum Si concentrations were identified, and the region satisfying the following equation was defined as the remaining intermediate layer region. (Si concentration in the region) > {(maximum Si concentration) + (minimum Si concentration)} / 2 The ratio of the total area of the defined intermediate layer remaining region to the total EDS mapping area of the delaminated portion was defined as the area ratio (%) of the intermediate layer remaining region. If the area ratio of the intermediate layer remaining region was 20% or more, it was judged to be acceptable as it met the requirements specified in the present invention. On the other hand, if the area ratio of the intermediate layer remaining region was less than 20%, it was judged to be unacceptable as it did not meet the requirements specified in the present invention. However, if the maximum and minimum Si concentrations satisfy the following equations, the area ratio of the remaining intermediate layer was considered to be 0%. (Maximum Si concentration) - (Minimum Si concentration) < 5 atoms %
[0147] [Water resistance test] Bending tests were performed on test specimens numbered 1 to 17 under the same conditions as the adhesion tests. The bent portion (bending region) of the test specimen was kept bent and the entire bending region was immersed in pure water for 1 minute. After 1 minute, the test specimen was removed. The test specimen was then dried. The test specimen was bent back to its original shape, and the area of the insulating film peeling after water immersion was calculated by image analysis. The peeling area due to water was calculated using the following formula. The results are shown in Table 1. (Area of peeling due to water) = (Area of insulation film peeling after water immersion) - (Area of insulation film peeling) The peeling area by water is 5.0 mm². 2 The following conditions were deemed to indicate excellent water resistance. On the other hand, the area of peeling due to water was 5.0 mm. 2 If it's "super," then I judged that it would have poor water resistance.
[0148] [Iron loss measurement] Based on JIS C 2550-1, the iron loss W17 / 50 (W / kg) was measured by the Epstein test at an excitation flux density of 1.7T and a frequency of 50Hz. An iron loss W17 / 50 of less than 1.00 was judged to be good. On the other hand, an iron loss W17 / 50 of 1.00 or more was judged to be poor.
[0149] Referring to Table 1, Tests 2, 4, 7, 8, 12, 14, and 15 showed a small area of insulation film peeling and an area ratio of 20% or more of the remaining intermediate layer, demonstrating excellent adhesion and water resistance. In particular, Tests 2, 4, 7, 8, 14, and 15 showed even better water resistance, with the area of peeling due to water being smaller than the area of insulation film peeling. Furthermore, these examples of inventions had an internal oxide number density of 0.020 particles / μm with an equivalent circle diameter of 0.1 μm or more. 2 The following conditions were observed, and iron loss was also good. Furthermore, in these examples of inventions, the arithmetic mean roughness Ra of the base steel plate surface was 1.0 μm or less, and the thickness of the intermediate layer was 2 to 400 nm. The arithmetic mean roughness Ra and the thickness of the intermediate layer were measured by the method described above.
[0150] On the other hand, in test numbers 1, 3, 5, 6, 11, 13, and 17, the degree of oxidation during the cooling process was less than 0.30. Therefore, the area ratio of the remaining intermediate layer was less than 20%, resulting in poor adhesion. In test numbers 1, 3, 5, 11, 13, and 17, the peeling area due to water was 5.0 mm². 2 It was extremely poor in terms of water resistance.
[0151] In test numbers 9 and 16, the degree of oxidation during the cooling process after finish annealing exceeded 100,000. As a result, internal oxides mainly composed of silicon oxide were formed, and the number density of these internal oxides was 0.020 particles / μm 2 It exceeded that limit. As a result, the low iron loss required for grain-oriented electrical steel sheets could not be obtained.
[0152] Test No. 10 showed a high MgO content in the annealing separation agent. As a result, internal oxides mainly composed of forsterite formed, and the number density of internal oxides with an equivalent circle diameter of 0.1 μm or more was 0.020 particles / μm 2 It exceeded that limit. As a result, the low iron loss required for grain-oriented electrical steel sheets could not be obtained. In test numbers 1, 3, 5, 6, 9, 10, 11, 13, and 16, the area of the insulating coating peeled off was also large.
[0153] Embodiments of the present invention have been described above. However, the embodiments described above are merely illustrative examples for carrying out the present invention. Therefore, the present invention is not limited to the embodiments described above, and the embodiments described above can be modified as appropriate without departing from the spirit of the invention. [Industrial applicability]
[0154] According to the present invention, it is possible to provide a grain-oriented electrical steel sheet having an intermediate layer mainly composed of silicon oxide, which exhibits high adhesion of the insulating film and high water resistance. Furthermore, the present invention provides an intermediate steel sheet for this grain-oriented electrical steel sheet and a method for manufacturing them.
Claims
1. A base steel plate, an intermediate layer formed on the surface of the base steel sheet and mainly composed of silicon oxide; an insulating coating formed on a surface of the intermediate layer, The number density of oxides in a region 10 μm deep from the surface of the base steel sheet toward the inside of the base steel sheet is 0.020 particles / μm 2 is as follows: After a bending test using a mandrel in accordance with JIS K 5600-5-1 (1999), the area ratio of the intermediate layer remaining area where the intermediate layer remains without peeling in the area where the insulating coating has peeled off is 20% or more. Grain-oriented electrical steel sheet.
2. a hot rolling process in which the slab is heated to 1280°C or less and then hot rolled to produce a hot-rolled steel sheet; a hot-rolled sheet annealing step of producing an annealed steel sheet by performing hot-rolled sheet annealing on the hot-rolled steel sheet; a cold rolling step of cold rolling the annealed steel sheet to produce a cold-rolled steel sheet; a decarburization annealing step of performing decarburization annealing on the cold-rolled steel sheet to produce a base steel sheet; an annealing separator application step of applying an annealing separator having a composition containing 50% by mass or more of alumina and the remainder 0 to 50% by mass of magnesia to the base steel sheet; a finish annealing step in which finish annealing is performed on the base steel sheet after the annealing separator application step; The base steel sheet after the final annealing step is subjected to oxidation at a temperature range of 1100 to 500°C, where the oxidation degree P is the ratio of the water vapor partial pressure to the hydrogen partial pressure. H2O / P H2 a cooling step of cooling the material in an atmosphere having a viscosity of 0.30 to 100,000; an intermediate layer forming step of heat treating the base steel sheet after the cooling step to form an intermediate layer mainly made of silicon oxide on the surface of the base steel sheet; and forming an insulating film on a surface of the intermediate layer after the intermediate layer forming step. Manufacturing method for grain-oriented electrical steel sheets.
3. A base steel plate, a film-like oxide formed on the surface of the base steel sheet; Equipped with The film-like oxide is present so as to cover the surface of the base steel sheet in the form of a film, The number density of oxides in a region 10 μm deep from the surface of the base steel sheet toward the inside of the base steel sheet is 0.020 particles / μm 2 Below is the Intermediate steel sheet for grain-oriented electrical steel sheets.
4. a hot rolling process in which the slab is heated to 1280°C or less and then hot rolled to produce a hot-rolled steel sheet; a hot-rolled sheet annealing step of producing an annealed steel sheet by performing hot-rolled sheet annealing on the hot-rolled steel sheet; a cold rolling step of cold rolling the annealed steel sheet to produce a cold-rolled steel sheet; a decarburization annealing step of performing decarburization annealing on the cold-rolled steel sheet to produce a base steel sheet; an annealing separator application step of applying an annealing separator having a composition containing 50% by mass or more of alumina and the remainder 0 to 50% by mass of magnesia to the base steel sheet; a finish annealing step of performing finish annealing on the base steel sheet after the annealing separator application step; The base steel sheet after the final annealing step is subjected to oxidation at a temperature range of 1100 to 500°C, where the oxidation degree P is the ratio of the water vapor partial pressure to the hydrogen partial pressure. H2O / P H2 a cooling step of cooling the material in an atmosphere having a viscosity of 0.30 to 100,000; Equipped with A manufacturing method for intermediate steel sheets for grain-oriented electrical steel sheets.
